Acrylamide Exposure Destroys the Distribution and Functions of Organelles in Mouse Oocytes - Zhao, Chao-Ying; Hu, Lin-Lin; Xing, Chun-Hua; Lu, Xiang; Sun, Shao-Chen; Wei, Yu-Xia; Ren, Yan-Ping (Frontiers in Cell and Developmental Biology, 2022)
Acrylamide (ACR) is a common industrial ingredient which is also found in foods that are cooked at high temperatures. ACR has been shown to have multiple toxicities including reproductive toxicity. Previous studies reported that ACR caused oocyte maturation defects through the induction of apoptosis and oxidative stress. In present study we showed that ACR exposure affected oocyte organelles functions, which might be the reason for oocyte toxicity. We found that exposure to 5 mM ACR reduced oocyte maturation. ACR caused abnormal mitochondria distribution away from spindle periphery and reduced mitochondrial membrane potential. Further analysis showed that ACR exposure reduced the fluorescence intensity of Rps3 as well as abnormal distribution of endoplasmic reticulum, indicating that ACR affected protein synthesis and modification in mouse oocytes. We found the negative effects of ACR on the distribution of Golgi apparatus; besides, fluorescence intensity of vesicle transporter Rab8A decreased, suggesting the decrease of protein transport capacity of oocytes. Furthermore, the simultaneous increase of lysosomes and LAMP2 fluorescence intensity were also observed, suggesting that ACR affected protein degradation in oocytes. In conclusion, our results indicated that ACR exposure disrupted the distribution and functions of organelles, which further affected oocyte developmental competence in mice.